THEORETICAL AND EXPERIMENTAL STUDY OF JET VECTORING IN SUBSONIC FLOW FOR CIRCULAR NOZZLE - Asady, A.A.A.; Alhafid, H.H.S (Journal of Advanced Manufacturing Technology (JAMT), 2015)
This paper presents theoretical and experimental investigations of thrust vectoring using co-flow method. The experimental investigation included a set of experiments carried out to demonstrate the ability to vector the exhaust flow in two axes (yawing and pitching angle) by secondary flow. A test rig was designed and constructed consisting of a circular duct in subsonic speed with four equals channels for secondary flow which represented the four directions of vectoring flow. And study the effect of various geometric variables on thrust vectoring angle. These included secondary slot height (h) and Coanda wall diameter (D) for a range of the mass flow ratio (ms/mp) (0 ≤ ms/mp ≤ 0.07882). Load measurements were obtained using four load cells. On the other hand, the theoretical investigation involved a 3D numerical solution by FLUENT Software for some of the experimental cases. The results showed that the thrust vectoring angle is proportional with the mass flow ratio and Coanda wall diameter, and inverse proportional with the secondary slot height. Three regions appear in the relationship curve between the mass flow ratio and thrust vectoring angle, that are “dead zone“ region, control region and saturation region.